2014
DOI: 10.1007/s00384-014-1960-5
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic ventral rectopexy in an elderly population with external rectal prolapse: clinical and anal manometric results

Abstract: Laparoscopic ventral rectopexy with posterior mobilisation seems to be effective and relatively well tolerated, although not without mortality in elderly debilitated patients. It improves incontinence. With increased life-year expectance, these patients may benefit from a lower risk of recurrence compared with perineal procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…There were 38 studies reporting the outcome of the use of mesh with rectopexy [13‐51] and one study reporting the outcome of resection suture rectopexy [45]. It was not possible to estimate the effect from pooled data in GRADE evidence due to lack of a comparator in all studies and one non‐mesh study with 0% recurrence.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…There were 38 studies reporting the outcome of the use of mesh with rectopexy [13‐51] and one study reporting the outcome of resection suture rectopexy [45]. It was not possible to estimate the effect from pooled data in GRADE evidence due to lack of a comparator in all studies and one non‐mesh study with 0% recurrence.…”
Section: Resultsmentioning
confidence: 99%
“…There were 30 studies that reported the outcome of the use of mesh with rectopexy [6,7,8,11,12,13,14,15,16,17,18,19,20,22,25,26,27,30,32,33,34,35,36,38,41,43,48,49,50,51]. The pooled recurrence rate in the biological mesh group was 4.5% while that in the synthetic mesh group was 4.6%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most patients were satisfied with the operation, but there was no association seen between satisfaction and functional result. 30 A German study from 2012 studied the outcome of LRR in elderly patients (> 75 years). The complication rate was slightly increased compared to the younger population.…”
Section: Laparoscopic Rectopexy In Elderly Patientsmentioning
confidence: 99%